Management of anxiety and depression disorders by university students during the covid-19 pandemic: A cross-sectional study (Revista Contexto & Saúde, 2025)
Objectives: to  evaluate the use of psychotropic drugs and/or psychotherapy for anxiety and/or depression management among Brazilian university students during the COVID-19 pandemic. Methods: a cross-sectional, quantitative study conducted by an online questionnaire containing sections related to sociodemographic data, academic information, mental health-related information, and evaluation of the  severity of anxiety and depression symptoms. Participants included university students aged 18 and older with a previous anxiety and/or depression disorders diagnosis. Descriptive and inferential analyses were performed. The study received approval from the Ethics Committee for Human Research. Results: 409 students with an anxiety and/or depression disorders diagnosis participated in the study. Most students reported using psychotropic drugs (62.3%; n = 255). There was no significant association between medication use and sociodemographic variables. Psychotherapy use was reported by 36.7% (n = 150) of students. A significant association was observed between psychotherapy use and ethnicity/color (p < 0.01) and engagement in paid activities (p = 0.02). Conclusion: The medication use prevalence is higher compared to psychotherapy use. Ethnicity/race and performance in paid activities may be associated with psychotherapy use among Brazilian university students.
Keywords: Anxiety; Depression; University students; Psychotropic drugs; Psychotherapy